Maxillary Fungal Osteomyelitis Mimicking and Treated as Endodontic Pathosis - Sarang Suresh Hotchandani; Feroze Ali Kalhoro; Priya Rani Harjani; Mahwish Memon (Hindawi Limited, 2022)
Fungal osteomyelitis is a lethal opportunistic infection that affects only a small percentage of patients present to endodontists. It is a highly contagious infection that requires urgent treatment. We discuss three cases in which endodontic pathology was initially recognized but subsequent follow-up revealed severe osteolytic fungal infection of the maxilla manifesting as acute apical abscesses in the maxillary canine region. CBCT demonstrated osteolytic abnormalities, and further histology confirmed the illness was caused by mucormycosis in patients with uncontrolled diabetes mellitus and exposure to COVID-19.